Co-expression of phenylalanine hydroxylase variants and effects of interallelic complementation on in vitro enzyme activity and genotype-phenotype correlation - Shen, Nan; Heintz, Caroline; Thiel, Christian; Okun, Jürgen G.; Hoffmann, Georg F.; Blau, Nenad (Molecular genetics and metabolism, 2016)
Background - In phenylketonuria (PKU) patients, the combination of two phenylalanine hydroxylase (PAH) alleles is the main determinant of residual enzyme activity in vivo and in vitro. Inconsistencies in genotype-phenotype correlations have been observed in compound heterozygous patients and a particular combination of two PAH alleles may produce a phenotype that is different from the expected one, possibly due to interallelic complementation. - Methods - A dual eukaryotic vector system with two distinct PAH proteins N-terminally fused to different epitope tags was used to investigate the co-expression of PAH alleles reported in patients with inconsistent phenotypes. PAH variant proteins were transiently co-transfected in COS-7 cells. PAH activity was measured by liquid chromatography-electrospray ionization tandem mass spectrometry (LC-ESI-MS-MS), and protein expression was measured by Western blot. Genotypes were compared with predicted PAH activity from the PAH locus-specific database (PAHvdb) and with phenotypes and tetrahydrobiopterin (BH4) responsiveness from more than 10,000 PKU patients (BIOPKU database). - Results - Through the expression and co-expression of 17 variant alleles we demonstrated that interallelic interaction could be both positive and negative. The co-expressions of p.[I65T];[R261Q] (19.5% activity; predicted 43.5%) and p.[I65T];[R408W] (15.0% vs. 26.8% activity) are examples of genotypes with negative interallelic interaction. The co-expressions of p.[E178G];[Q232E] (55.0% vs.36.4%) and p.[P384S];[R408W] (56.1% vs. 40.8%) are examples of positive subunit interactions. Inconsistencies of PAH residual enzyme activity in vitro and of PKU patients' phenotypes were observed as well. The PAH activity of p.[R408W];[A300S] is 18.0% of the wild-type activity; however, 88% of patients with this genotype exhibit mild hyperphenylalaninemias (MHPs). - Conclusion - The co-expression of two distinct PAH variants revealed possible dominance effects (positive or negative) by one of the variants on residual PAH activity as a result of interallelic complementation.
Gesehen am 28.02.2020